Functional cognitive impairment: A new concept in neuropsychiatry - Reza Bidaki; Zanire Salimi (روانشناسی و روانپزشکی شناخت, 2023)
Due to the high prevalence of different levels of memory disorders and amnesia, many psychiatry and psychology referrals are due to the fear of diseases that cause dementia, including Alzheimer's disease. However, many of these disorders have internal causes and can be classified as functional cognitive disorders. Although the diagnosis of cognitive disorder is made by ruling out organic causes, it is difficult to diagnose functional disorders, thus most of these disorders are not diagnosed. It has been determined that depression, anxiety and behavioral disorders can be precursors of mild cognitive impairment, but it has not been determined whether functional cognitive impairment can also be a trigger or precursor for organic cognitive disorders related to dementia. The typical form of functional cognitive disorder overlaps with the components of attention and concentration. The coexistence of these disorders with depression can make the diagnosis of functional cognitive disorders more difficult. Therefore, it is important to rule out pseudodementia due to depression before making such a diagnosis. Since functional cognitive impairment occur in the midlife period, these disorders are differentially diagnosed with early-onset neurodegenerative disorders. Regardless of the research conducted in the field of diagnosing functional cognitive disorders, no definitive diagnostic criteria have been determined for these disorders, and the long-term prognosis of these disorders is also unknown.